Low oxygen tension is a more potent promoter of chondrogenic - KELLY, DANIEL; BUCKLEY, CONOR (My University, 2010)
During fracture healing and microfracture treatment of cartilage defects mesenchymal stem cells (MSCs) infiltrate the wound site, proliferate extensively and differentiate along a cartilaginous or an osteogenic lineage in response to local environmental cues. MSCs may be able to directly sense their mechanical environment or alternatively, the mechanical environment could act indirectly to regulate MSC differentiation by inhibiting angiogenesis and diminishing the supply of oxygen and other regulatory factors. Dynamic compression has been shown to regulate chondrogenesis of MSCs. In addition, previous studies have shown that a low oxygen environment promotes in vitro chondrogenesis of MSCs. The hypothesis of this study is that a low oxygen environment is a more potent promoter of chondrogenic differentiation of MSCs embedded in agarose hydrogels compared to dynamic compression. In MSC-seeded constructs supplemented with TGF-?3, GAG and collagen accumulation was higher in low oxygen conditions compared to normoxia. For normoxic and low oxygen culture GAG accumulation within the agarose hydrogel was inhomogeneous, with low levels of GAG measured in the annulus of constructs maintained in normoxic conditions. Dynamic compression did not significantly increase GAG or collagen accumulation in normoxia. However under low oxygen conditions, dynamic compression reduced GAG accumulation compared to free-swelling controls, but remained higher than comparable constructs maintained in normoxic conditions. This study demonstrates that continuous exposure to low oxygen tension is a more potent prochondrogenic stimulus than one hr/day of dynamic compression for porcine MSCs embedded in agarose hydrogels.
PUBLISHED
PMID: 20557888
Keywords: Bioengineering; Mesenchymal stem cells; Mechanobiology; Dynamic compression; Oxygen tension; Fracture healing; Next Generation Medical Devices